Jamming Anti-Ship Missile Seekers Which Use Doppler Beam Sharpening Modes - Frazer, Gareth (Cranfield University, 2017)
3MT presented at the 2017 Defence and Security Doctoral Symposium.This PhD investigates the concept of jamming missile seekers which use a Doppler Beam Sharpening (DBS) mode for target detection and homing. DBS provides a computationally efficient way of improving the cross-range resolution by using the Doppler domain to resolve targets that could not otherwise be resolved with a typical real beamed pulsed radar system. The PhD explores how to use low cost jammers to accurately place false targets in a desired location in the DBS image and the problems which arise when there is a lack of knowledge about seeker trajectory, velocity, waveforms used, etc.
Keywords: 'Doppler Beam Sharpening'; 'Jamming'; 'Radar'; 'DSDS17 3MT'; 'DSDS17'; 'Defence Studies'